Factor Analysis to Form Customer Satisfaction on Building Material Retail - Alvin Livano; Eric Harianto (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
This study aims to determine the factors that shape consumer satisfaction that focuses on retailed building materials. In this study, the case raised is based on retail business UD Semeru (UDS) in Surabaya. There are 27 variables used as factors that are assumed to form consumer satisfaction. The results of this study will be used by UDS to develop a strategic framework that shapes the success of UDS. This research will be based on quantitative research, and uses 71 people as samples. The analytical method that is used is exploratory factor analysis (EFA) by interpreting the data in SPSS application. The results of this study show that tangible factors are the main factor that forms UDS’s customer satisfaction, and the intangible factors show a supporting factor that forms UDS customer satisfaction.